Phase change with voids and bubbles - Ascione, Francesco; Frémond, Michel (Vietnam Journal of Mechanics, 2009)
We investigate phase transition at the macroscopic level. The main novelty of our approach is the possibility of having voids during the phase change. This aspect is described in the model by the mass balance equation which results in a pressure which has a paramount importance. The state variables are the temperature, the strain tensor, and the volume fractions of the two phases (whose evolutions are described by a vectorial equation coming from the principle of virtual power and related to microscopic motion responsible for the phase change). The theory accounts for the main physical phenomenons, for instance, for the cavitation phenomenon and for pressure dependance of the phase change temperature. The scope of the predictive theory is illustrated with uni-dimensional examples.